Amos 'n' Andy radio program scripts
Amos 'n' Andy radio program scripts submitted to the Library of Congress Copyright Office between 1928 and 1937.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Radio programs; Radio scripts